Chronic pain in hypertension in adults: a bibliometric study (Research, Society and Development, 2020)
Introduction: there is a relationship between chronic non-communicable diseases (CNCD) and chronic pain. And as among these diseases, there is an estimate that hypertension affects 36 million Brazilians, the importance of the study is inferred. Therefore, the objective was to analyze the bibliometric indicators of dissertations and theses on conical pain in hypertension in Brazilian territory. Methodology: this is a bibliometric study carried out at the Bank of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES) and at the Brazilian Digital Library of Theses and Dissertations (BDTD), between the years 2010 to 2020 in Brazil. Data collection took place from October to November 2020, using the keywords "chronic pain" and "hypertension", with subsequent elaboration of a conceptual map from the research descriptors. Results: of the 982 studies identified, only 20 met the inclusion criteria, including 4 theses and 16 dissertations, using the quantitative approach. Final Considerations: the relationship between chronic pain and hypertension was observed, however, showing a small number of studies. Thus, further investigations are necessary.